La teoría de la acción en Weber, Parsons y Habermas: algunas consideraciones críticas - López Moreno, Ángeles (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2005)
One of the main mistakes of the discussion about action consists of focusing the attention on the concept of meaning. Hidden by phenomenological, hermeneutic, linguistic or functional interpretations of meaning, this action is considered from an external perspective (observation), being only perceptible from the point of view of an observer who is not the same acting subject. However, we forget that the action relates to the subject’s free decision who gives full meaning to is own decision-making to act according to a complex process of thought, while considering the external transcendence that the action may have for him or her and for other people. It all starts with Weber’s sociological theory —from the human action to the social action— and culminates with J. Habermas’ sociological and communicative theory. This study aims at critically explaining such theories.